Critical thinking in cognitive domain: Exploring assessment of English teaching at pandemic period of covid-19 - Akib, Erwin; Muhsin, Muh. Arief (JEES (Journal of English Educators Society), 2020)
Assessment is an evaluation tool in learning adjusted to the times. The criteria must be included in the assessment are indicators in the cognitive domain and critical thinking. Therefore, this study intends to explore teaching assessments prepared by lecturers in assessing students' cognitive shutter and critical thinking abilities. The data took in the pandemic period of pandemic in Covid-19. The subjects of this study were 269 lecturers who teaching in English education departments in some Muhammadiyas’ university in South Sulawesi. There were 25 items of questionnaires arranged to analyses the teacher assessment based on 10 indicators in critical thinking. The results showed the dominant lecturer measured the ability of students on the C1-C2 scale even though some lecturers had been on the C5-C6 scale. The lecturer learning assessment has implemented indicators of critical thinking skills. The study recommended for future researcher in developing assessment of teaching especially for English department.